FILSAFAT PENDIDIKAN ISLAM TENTANG KURIKULUM - Nuriyanti, Nuriyanti (State Institute of Islamic Studies (IAIN) Palu, 2008)
The philosophy of Islamic education plays a vital role in guiding the general objective of education and directing Islamic education as well in order that the curriculum, which consists of values, can be in line with the universally accepted truth. Compared to other curriculums, Islamic education has its own different characteristics since it is based on the principles and materials derived from the Qur’an and the prophetic traditions.Kata Kunci: filsafat, pendidikan Islam, kurikulum